Environmental Damage in The Novel of Serdadu Pantai by Laode Insan: A Study of Ecocriticism - Fadli, Bagus Muhamad; Yuniawan, Tommi; Nuryatin, Agus (Universitas Negeri Semarang, 2021)
Humans easily exploit the nature because their ethics towards the environment is based on the anthropocentrism perspective. Marine pollution and environmental damage for the sake of individual or certain groups economic satisfaction indicate a lack of human awareness to protect the environment. These activities are the cause of the environmental damage in the Serdadu Pantai novel by Laode Insan. This study aims to find out and describe ecocriticism in the Serdadu Pantai novel by Laode Insan related to the environmental damage, the behavior of the characters causing the environmental damage, and social and economic backgrounds as a factor in the occurrence of the environmental damage in the novel of Serdadu Pantai by Laode Insan. This study applies a qualitative research employing an ecocriticism approach. The primary data source of this study is the Serdadu Pantai novel by Laode Insan published by PT Grasindo in 2019. The data in this study is a fragment of the text of the Serdadu Pantai novel by Laode Insan which allegedly contains ecological criticism. The secondary data sources are journals and books related to environmental ecology and literary ecocriticism. The results show that; (1) the environmental damage in the Serdadu Pantai novel was demonstrated through coral reefs damage and water pollution caused by the behavior of people who utilize natural resources in a way that is not in accordance with the concept of conservation, such as using trawlers, poisons, and bombs to catch fish, and also through the characters’ way of thinking toward the environment; (2) the social and economic background as a factor in the occurrence of the environmental damage was demonstrated through a social background that lacks education about nature conservation which later gives impact on long-term environmental damage. Economic problems of livelihoods that depend on marine resources as the main source of income have also created excessive exploitative behavior of the community which causes damage to the marine ecosystems.